Empowering Song: a music education approach to marginalized people (Per Musi, 2024)
The aim of this study is to explore which aspects of the Empowering Song approach have been used in the process of teaching and learning music to marginalized people and how these activities can affect them, changing their attitudes and helping them to understand themselves and others, and how this can help build community. The methods used for data collection were as follows: bibliographical research, a questionnaire, semi-structured interviews, and observation at meetings of the Race, Prison, Justice, Arts project, the Voices21C choir and the Empowering Song: music with body, mind and heart course. The result of the data analysis was the organization of the activities into four categories: musical-educational, philosophical, psychological, and sociological aspects. The conclusion was that the Empowering Song approach profoundly impacts marginalized people through its interdisciplinarity, functioning as a means of social justice, allowing them to find themselves as artists and express themselves through art.